Predicting changes in hemoglobin S after simple transfusion using complete blood counts. Issue 1 (11th October 2017) - Mathur, Gagan; Ten Eyck, Patrick; Knudson, C. Michael
Abstract : BACKGROUND: Hemoglobin S percentages are used in the management of patients who have sickle cell disease. However, hemoglobin S measurements often are not routinely or rapidly performed. Rapid and accurate methods to estimate hemoglobin S levels after simple transfusion may improve the care of patients with sickle cell disease. STUDY DESIGN AND METHODS: A comprehensive review of the electronic medical record identified 24 stable patients with sickle cell disease who received simple red blood cell transfusions and had hemoglobin S measurements before and after the transfusion that were less than 72 hours apart. Examination of these patients identified 62 separate transfusions that met our criteria. Three simple equations that utilized complete blood count values and readily available information from the medical record were used to predict the post‐transfusion hemoglobin S level after transfusion (Equation 1: predicted post‐transfusion hemoglobin = pre‐transfusion hemoglobin S × [pre‐transfusion hemoglobin/post‐transfusion hemoglobin]; Equation 2: predicted post‐transfusion hemoglobin S = pre‐transfusion hemoglobin S × [pre‐transfusion hematocrit/post‐transfusion hematocrit]; and Equation 3: predicted post‐transfusion hemoglobin S = pre‐transfusion hemoglobin S × total pre‐transfusion hemoglobin/[total pre‐transfusion hemoglobin + (red blood cell volume × 20)]). RESULTS: The predicted hemoglobin S values for all three equations showed a highly significant correlation with the measured post‐hemoglobin S value. The coefficient of determination (R 2 ) for Equations 1, 2, and 3 was 0.95, 0.92, and 0.97, respectively. Predicting the post‐transfusion hemoglobin S value using estimates of the patient's total hemoglobin and the transfused hemoglobin (Equation 3) was the most precise. CONCLUSION: Reductions in hemoglobin S values in patients with sickle cell disease who receive simple red blood cell transfusions can be reliably predicted using complete blood cell measurements and simple arithmetic equations.